MISKONSEPSI PENGGUNAAN TANDA BACA SEBAGAI KOMPOTENSI LITERASI MEMBACA KELAS V SDN MEDONO 04 PEKALONGAN - Slamanda; Iin Purnamasari; Husni Wakhyudin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Misconceptions in learning Indonesian language on punctuation, often experienced by students are misconceptions in the use of punctuation, especially in the placement of commas which are the most common errors in writing, then periods, exclamation marks, and questions. This study aims to identify forms of misconceptions in students in the use of punctuation, factors causing misconceptions in the use of punctuation, and solutions to overcome misconceptions in the use of punctuation in class V SDN Medono 04 Pekalongan. Data collection techniques used observation techniques, interviews, student worksheet results, questionnaires, and documentation. The results of the study showed that misconceptions of punctuation were mainly caused by a lack of understanding of basic concepts, inappropriate writing habits, and minimal practice. The solution to overcoming misconceptions in the use of punctuation is that teachers provide writing exercises using punctuation, give quizzes by completing sentences with the correct punctuation, and get students used to reading texts with intonation according to punctuation. These findings are expected to be a reference for educators in improving students' understanding of the use of punctuation correctly.